Diffuser in Fractional Fourier Optics (2016)
We propose a method for calculating a bandlimited diffuser with smooth spectrum in the Fresnel domain without any 2p phase ambiguities using the fractional Fourier transform. Such diffusers are necessary to avoid problems of speckles. © OSA 2016.